A Prosa Do Mundo E A Poesia Do Coração: Aspectos Do Legado Hegeliano Na Teoria Do Romance De Lukács - Oliveira, Flavio Cunha Dias De [UNIFESP] (2017)
The goal of this work is to present the Theory of the Novel from Georg Lukács under the lights of the classical poetry of genders and, in particular, the influence of the Hegelian legacy on the esthetics formation of the Hungarian philosopher, highlighting the main idea of the novel such as proposed by Georg Wilhelm Friedrich Hegel: namely, the collision among the social relations prose (the prose of the world) and the poetry of the heart. Both authors conceive the novel as the epopee from the modern era, though they diverge in the historical-philosophical meaning of this esthetical situation. For this purpose, it is presented the foundations of the traditional aesthetics and its inversion from the dialectical movement in what Hegel put the classical poetry of gender from an Aristotelian basis through. After that, the work moves to the body of the text of the Theory of the Novel, recomposing the arguments from the author under the lights of the esthetical philosophy and the “science of the spirits” from Hegel, since its esthetical convergence until the divergence of social nature among the authors, about the meaning of the novel as a literary experience from modernity, especially the theme of the reconciliation or the no reconciliationof the poetry of the heart with the prose of the world. Finally, the work of the German poet, Johann Wolfgang Von Goethe, Wilhelm Meister’s Apprenticeship (Wilhelm Meisters Lehrjahre), is used as a significant literary representation to express the content and the meaning of the novel, being either about the whole of the gender and the essential division that gives rises to it, or as a particular development, the novel of German formation (Bildungsroman), typical from the end of the XVIII century.